The endocannabinoid system and ophthalmic pathologies: a review of molecular mechanisms and its implications for clinical practice - Charytoniuk, Tomasz; Półjanowski, Stanisław; Michalak, Mateusz; Kaźmierczak, Karolina; Kałużny, Bartłomiej (Frontiers in Medicine, 2025)
Within the last decade the role of the endocannabinoid system (ECS) has been a significant part of ophthalmic research, including both ocular physiology and the development of eye pathologies. It is known that this widespread cell-signaling system is involved in retinal neurobiological processes, including visual signal processing, as well as neurotransmission. Furthermore, various research indicated the involvement of ECS in the molecular basis of various pathologies, mostly glaucoma, diabetic retinopathy, and age-related macular degeneration (AMD). Therefore, the researchers believe that this biological system, its receptors, pathways, and ligands might be considered as an auxiliary compound to reduce the number of patients suffering from ophthalmic diseases. Despite presented in the literature effects of the endocannabinoid system in the eye, none of the current ECS reviews presented a comprehensive description of the endocannabinoid system, its compounds, and, subsequently ophthalmic disorders. Thus, the aim of this review was to summarize all the major data, including the most up-to-date research, concerning a correlation between the endocannabinoid system and the major ophthalmic pathologies.